Outbreak of Acinetobacter baumannii associated with extrinsic contamination of ultrasound gel in a tertiary centre burn unit - Kruti J. Yagnik; Gautam Kalyatanda; Anthony P. Cannella; Lennox K. Archibald (Elsevier, 2019)
Summary: Background: During 2011 and 2012, an increase in occurrence of multidrug-resistant Acinetobacter baumannii infections was recorded in the Shands Hospital Burn Intensive Care Unit (BICU). An epidemic curve together with strain typing was consistent with an intermittent common source outbreak. An investigation was therefore initiated. Aim: To identify risk factors for A. baumannii infection, characterize the source of the pathogen, implement control measures to terminate the outbreak, and institute preventive measures. Methods: We conducted a retrospective case-control study; reviewed BICU infection control policies, practices and procedures, and patient exposure to healthcare workers (HCWs), and obtained epidemiologically-directed environmental cultures. Findings: Eleven patients met the case definition. On multivariate analysis, case-patients were more likely to have undergone an ultrasound procedure in the BICU (adjusted odds ratio [AOR]: 19.5; confidence interval [CI]: 2.4-435) or have a FlexiSeal™ device (AOR: 11.9, CI:1.3-276). Epidemiologically-directed cultures of the environment, ultrasound equipment, and ultrasound gel from opened containers on the ultrasound trolley and in the Ultrasound Department were negative for the outbreak pathogen. Culture of an open ultrasound gel dispenser stored in the Ultrasound Department yielded an A. baumannii strain with DNA banding patterns identical to the outbreak strain. Conclusions: Based on data from our epidemiologic, microbiologic, and observational studies, we believe that inadvertent extrinsic contamination of the gel dispenser occurred in the Ultrasound Department. Contaminated gel was then dispensed into multiuse vials of gel stored on the mobile carts. The outbreak was stemmed by instituting changes in practices in the Ultrasound Department, including introduction of single-use ultrasound vials and storage of ultrasound gel. Keywords: Acinetobacter baumannii, Ultrasound gel, Outbreak, Nosocomial infection, Burn unit